2019
DOI: 10.1186/s43055-019-0058-z
|View full text |Cite
|
Sign up to set email alerts
|

What can DTI add in acute ischemic stroke patients?

Abstract: Background: Cerebrovascular stroke is one of the leading causes of death worldwide. Imaging with conventional MR techniques cannot provide reliable information as regard the integrity of the white matter tracts and therefore limiting its ability to predict the clinical outcome. While prediction of the motor outcome becomes more crucial for determining the specific rehabilitation strategies and final clinical outcomes, the purpose of this study was to assess the value of diffusion tensor MR imaging in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…However, after post hoc pairwise comparisons, only subjects with an mRS of 2 (slight disability) had lower FA in NAWM than subjects with an mRS of both 0 (no symptoms) and 1 (no significant disability, despite some symptoms) (Figure 7(b)). This result is consistent with previous studies that have reported correlation between FA in NAWM or in the tracts affected by stroke lesions and mRS in stroke patients [15,[83][84][85][86]. Our results specifically suggest that structural disruptions in normal-appearing WM are different depending on the level of disability and dependence in people with CVD.…”
Section: Discussionsupporting
confidence: 93%
“…However, after post hoc pairwise comparisons, only subjects with an mRS of 2 (slight disability) had lower FA in NAWM than subjects with an mRS of both 0 (no symptoms) and 1 (no significant disability, despite some symptoms) (Figure 7(b)). This result is consistent with previous studies that have reported correlation between FA in NAWM or in the tracts affected by stroke lesions and mRS in stroke patients [15,[83][84][85][86]. Our results specifically suggest that structural disruptions in normal-appearing WM are different depending on the level of disability and dependence in people with CVD.…”
Section: Discussionsupporting
confidence: 93%
“…FA, which measures the directionality of molecular displacement by diffusion, is used to infer white matter tract integrity. FA is often decreased in major white matter tracts post-stroke due to microstructural damage and loss of structural integrity resulting from local tissue damage and/or retrograde axonal degeneration ( 46 , 47 ). The asymmetrical decrease in FA may potentially be due to differences in white matter resilience, such that YC white matter is more refractory to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in both interhemispheric functional connectivity (FC) and ipsilesional CST-FA were significantly correlated with the greater change of Fugl–Meyer Assessment (FMA) between weeks 1 and 4 post-stroke. In line with these findings, Mahmoud and colleagues [ 37 ] studied a cohort of 60 acute ischemic stroke patients within 2 days from onset. In patients with intact WM tracts, near-complete clinical recovery was noted.…”
Section: Discussionmentioning
confidence: 84%
“…One study does did provide information regarding field strength [ 30 ]. With regards to the number of directions, three studies used 6 directions (two in 1.5 T [ 34 , 35 ] and one in 3.0 T [ 36 ]), eight studies used 12 directions (four in 1.5 T [ 37 , 38 , 39 ] and four in 3.0 T [ 40 , 41 , 42 , 43 ]), three studies used 15 directions (two in 1.5 T [ 44 , 45 ] and one in 3.0 T [ 23 ]), three studies used 16 directions (one in 1.5 T [ 46 ] and two in 3.0 T [ 24 , 47 ]), one study in 1.5 T used 20 directions [ 31 ], one study in 3.0 T used 25 directions [ 48 ], eight studies used 30 directions (two in 1.5 T [ 49 , 50 ] and six in 3.0 T [ 18 , 29 , 33 , 51 , 52 , 53 ]), three studies in 1.5 T used 32 directions [ 54 , 55 , 56 ], one study in 3.0 T used 55 directions [ 57 ], and seven studies in 3.0 T used 64 directions [ 25 , 26 , 27 , 32 , 58 , 59 , 60 ]). Six studies did not provide information regarding diffusion directions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation